2013
DOI: 10.4049/jimmunol.1202482
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CXCR3 on Specific T Cells Is Essential for Homing to the Prostate Gland in an Experimental Model of Chronic Prostatitis/Chronic Pelvic Pain Syndrome

Abstract: Experimental autoimmune prostatitis (EAP) is considered a valid model for the human disease chronic prostatitis/chronic pelvic pain syndrome. In this report, we analyzed phenotypic characteristics of T cells that gain access to the prostate and induce leukocyte recruitment in mice with different susceptibility to EAP. After EAP induction, NOD mice developed a specific cellular response characterized by a mixed Th1/Th17 pattern with specific T cells mainly expressing CXCR3 that infiltrated and damaged the prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(125 citation statements)
references
References 48 publications
4
120
0
1
Order By: Relevance
“…Microarray studies showed that Ccl5 and Cxcl9 / 10 were the only T cell chemokines induced after romidepsin treatment (Table S2). To examine whether T cell recruitment was necessary for the anti-tumor effect of romidepsin, we pre-treated mice with TAK-779, an inhibitor of CCR5 and CXCR3 (26), the receptors of CCL5 and Cxcl9 / 10/11 , respectively. TAK-779 prevented the romidepsin-induced increase in T cell density (CD4: 1.4% to 0.9% and CD8: 2.7% to 1.2%), but did not reduce steady state T cell numbers (CD4: 0.6% to 0.8% and CD8: 0.9 to 1.0%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Microarray studies showed that Ccl5 and Cxcl9 / 10 were the only T cell chemokines induced after romidepsin treatment (Table S2). To examine whether T cell recruitment was necessary for the anti-tumor effect of romidepsin, we pre-treated mice with TAK-779, an inhibitor of CCR5 and CXCR3 (26), the receptors of CCL5 and Cxcl9 / 10/11 , respectively. TAK-779 prevented the romidepsin-induced increase in T cell density (CD4: 1.4% to 0.9% and CD8: 2.7% to 1.2%), but did not reduce steady state T cell numbers (CD4: 0.6% to 0.8% and CD8: 0.9 to 1.0%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…88 Prostate inflammation has also been examined histologically, 3 with data to show increased leukocyte infiltration and increased numbers of T cells (more specifically, CD8 + T cells) compared with controls. 89 …”
Section: Cytokine and Chemokine Associationmentioning
confidence: 99%
“…It has been indicated the levels of IFN-γ, TNF-α and IL-1β were elevated in the semen of CP / CPPS-suffering patients [20]. IFN-γ/STAT1 signaling pathway has also been shown plays an important role in the immune responses to prostatitis in experimental autoimmune prostatitis mouse model [21]. However the researches about whether the testosterone reduces the prostatitis and the regulated mechanism relate to IFN-γ/STAT1 signaling pathway both remain lacked.…”
Section: Introductionmentioning
confidence: 99%